Multilayer Ceramic Capacitors

By using a barium titanate-based dielectric ceramic composition in a multi-layer ceramic capacitor and adjusting the contents of dysprosium (Dy) and praseodymium (Pr), the problems of deterioration of dielectric layer reliability and insulation resistance are solved, and high capacitance and miniaturization are achieved.

CN115483026BActive Publication Date: 2025-03-28SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211320033.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-24
Filing Date
2020-04-27
Publication Date
2025-03-28
Estimated Expiration
2040-04-27

AI Technical Summary

Technical Problem

The existing multi-layer ceramic capacitors are difficult to take into account between miniaturization and high capacitance requirements, and the reliability of the dielectric layer and the deterioration of the insulation resistance have become problems.

Method used

A dielectric ceramic composition with the main component of barium titanate (BaTiO3) base matrix material and dysprosium (Dy) and praseodymium (Pr) as sub-components was used to improve the dielectric constant and insulation resistance by adjusting the content of praseodymium (Pr) (0.233 mol % ≤ Pr ≤ 0.699 mol %).

Benefits of technology

The high k dielectric constant and insulation resistance are improved, ensuring the reliability and high capacitance performance of multi-layer ceramic capacitors, while allowing the thickness of the dielectric layer and inner electrode to be reduced, meeting the needs of miniaturization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115483026B_ABST
    Figure CN115483026B_ABST
Patent Text Reader

Abstract

A multilayer ceramic capacitor is provided. The multilayer ceramic capacitor comprises a ceramic body, the ceramic body comprises a dielectric layer, the dielectric layer comprises dielectric grains containing a dielectric ceramic composition, the dielectric ceramic composition comprises a main component of a matrix material and a secondary component, the main component of the matrix material comprises BaTiO3, (Ba 1‑x Ca x )(Ti 1‑y Ca y )O3(0≤x≤0.3, 0≤y≤0.1), (Ba 1‑x Ca x )(Ti 1‑y Zr y )O3(0≤x≤0.3, 0≤y≤0.5) and Ba(Ti 1‑y Zr y )O3(0
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with the application date of April 27, 2020 and application number 202010342515.5 and the invention name “Dielectric ceramic composition and multilayer ceramic capacitor including the same”. Technical Field

[0002] The present disclosure relates to a dielectric ceramic composition and a multilayer ceramic electronic component including the dielectric ceramic composition. Background Art

[0003] Electronic components using ceramic materials, such as capacitors, inductors, piezoelectric elements, varistors, thermistors, etc., include a ceramic body formed using the ceramic material, internal electrodes formed in the ceramic body, and external electrodes mounted on a surface of the ceramic body to be connected to the internal electrodes.

[0004] As there is a recent trend toward miniaturization and multifunctionalization of electronic products and chip components, there is a need for a multilayer ceramic capacitor that is smaller in size but has greater capacitance.

[0005] A method of miniaturizing a multilayer ceramic capacitor while increasing its capacitance is to reduce the thickness of the dielectric layer and the internal electrode layer to stack a greater number of layers. Currently, the thickness of the dielectric layer is about 0.6 μm, and efforts have been made to develop thinner dielectric layers.

[0006] Under such circumstances, ensuring the reliability of the dielectric layer is becoming a major issue for dielectric materials. In addition, as the degradation of the insulation resistance of the dielectric material increases, difficulties in managing quality and yield are becoming a problem.

[0007] In order to solve such problems, it is necessary to develop a new method for ensuring high reliability not only for the structure of the multilayer ceramic capacitor but also for the dielectric composition.

[0008] When a dielectric composition capable of improving current reliability is secured, thinner multilayer ceramic capacitors can be manufactured. Summary of the invention

[0009] An aspect of the present disclosure is to provide a dielectric ceramic composition capable of improving reliability and a multilayer ceramic capacitor including the same.

[0010] According to one aspect of the present disclosure, a dielectric ceramic composition includes a barium titanate (BaTiO3)-based matrix material main component and a subsidiary component, wherein the subsidiary component includes dysprosium (Dy) and praseodymium (Pr) as a first subsidiary component. Based on 100 mol % of the barium titanate-based matrix material main component, the content of Pr satisfies 0.233 mol % ≤ Pr ≤ 0.699 mol %.

[0011] According to another aspect of the present disclosure, a multilayer ceramic capacitor includes: a ceramic body including a dielectric layer and a first inner electrode and a second inner electrode, the first inner electrode and the second inner electrode are arranged to face each other and the corresponding dielectric layer is interposed between the first inner electrode and the second inner electrode; and a first outer electrode and a second outer electrode are arranged on the outer surface of the ceramic body, the first outer electrode is connected to the first inner electrode and the second outer electrode is connected to the second inner electrode. The dielectric layer contains dielectric grains containing a dielectric ceramic composition. The dielectric ceramic composition includes a main component and a subcomponent of a barium titanate (BaTiO3)-based matrix material, and the subcomponent includes dysprosium (Dy) and praseodymium (Pr) as a first subcomponent. Based on 100 mol% of the main component of the barium titanate-based matrix material, the content of Pr satisfies 0.233 mol%≤Pr≤0.699 mol%. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] The above and other aspects, features and advantages of the present disclosure will be more clearly understood through the following detailed description taken in conjunction with the accompanying drawings, in which:

[0013] Figure 1 is a schematic perspective view of a multilayer ceramic capacitor according to an example in the present disclosure;

[0014] Figure 2 It is along Figure 1 A cross-sectional view taken along line II′ of ; and

[0015] Figure 3 is a graph showing temperature-dependent dielectric constant results according to embodiments and comparative examples in the present disclosure. DETAILED DESCRIPTION

[0016] Hereinafter, embodiments of the present disclosure will be described as follows with reference to the accompanying drawings. However, the present disclosure may be presented in many different forms and should not be construed as being limited to the embodiments set forth herein. More specifically, these embodiments are provided so that the present disclosure will be thorough and complete, and the scope of the present disclosure will be fully communicated to those skilled in the art. In the accompanying drawings, for the sake of clarity, the shapes and sizes of the elements may be exaggerated, and the same reference numerals will always be used to indicate the same or similar elements.

[0017] Figure 1 is a schematic perspective view of a multilayer ceramic capacitor according to an embodiment in the present disclosure.

[0018] Figure 2 It is along Figure 1 A cross-sectional view taken along line II′.

[0019] Reference Figure 1 and Figure 2The multilayer ceramic capacitor 100 according to the embodiment includes: a ceramic body 110 including a dielectric layer 111 and first and second internal electrodes 121 and 122 disposed to face each other with the respective dielectric layers interposed therebetween; and first and second external electrodes 131 and 132 disposed on outer surfaces of the ceramic body 110. The first external electrode 131 is electrically connected to the first internal electrode 121, and the second external electrode 132 is electrically connected to the second internal electrode 122.

[0020] Regarding the multilayer ceramic capacitor 100 according to the embodiment, the "length direction", "width direction" and "thickness direction" will be defined as the "L" direction, the "W" direction and the "T" direction, respectively. The "thickness direction" may be used in the same meaning as the direction along which dielectric layers are stacked (e.g., the "stacking direction").

[0021] Although not limited to a specific shape, the configuration of the ceramic body 110 may be a rectangular cuboid shape as shown in the drawings.

[0022] The plurality of internal electrodes 121 and 122 formed inside the ceramic body 110 have one end exposed to one surface of the ceramic body 110 or the other surface of the ceramic body 110 disposed opposite to the one surface.

[0023] The internal electrodes 121 and 122 may include a pair of a first internal electrode 121 and a second internal electrode 122 having opposite polarities to each other.

[0024] One end of the first internal electrode 121 may be exposed to one surface of the ceramic body, and one end of the second internal electrode 122 may be exposed to the other surface of the ceramic body disposed opposite to the one surface.

[0025] The first and second external electrodes 131 and 132 are disposed on one surface and the other surface of the ceramic body 110 disposed opposite to each other to be electrically connected to the internal electrodes.

[0026] The material of the first and second internal electrodes 121 and 122 is not limited, and may be a conductive paste including, for example, at least one of silver (Ag), lead (Pb), platinum (Pt), nickel (Ni), and copper (Cu).

[0027] The first and second external electrodes 131 and 132 may be electrically connected to the first and second internal electrodes 121 and 122, respectively, to form capacitance. The second external electrode 132 may be connected to a potential different from that connected to the first external electrode 131.

[0028] The conductive material included in the first and second external electrodes 131 and 132 is not limited, but may be nickel (Ni), copper (Cu), or an alloy thereof.

[0029] The thickness of the first and second external electrodes 131 and 132 may be appropriately determined according to their uses, etc., without limitation, and may be, for example, 10 μm to 50 μm.

[0030] According to an embodiment, the material of the dielectric layer 111 is not limited as long as sufficient capacitance can be obtained, and may be, for example, barium titanate (BaTiO 3 ) powder particles.

[0031] The material of the dielectric layer 111 may include various additives added to BaTiO 3 powder particles, etc., an organic solvent, a plasticizer, a binder, a dispersant, etc.

[0032] The dielectric layers 111 in the sintered state may be integrated with each other so that the boundaries between adjacent dielectric layers 111 may not be apparent.

[0033] The first and second internal electrodes 121 and 122 may be formed on the dielectric layer 111 , and the internal electrodes 121 and 122 may be formed inside the ceramic body 110 together with the dielectric layer interposed therebetween by sintering.

[0034] The thickness of the dielectric layer 111 may be selectively changed according to the capacitance design of the capacitor. In an embodiment, in particular, the thickness of each dielectric layer after sintering may be 0.4 μm or less.

[0035] In addition, specifically, the thickness of the first internal electrode 121 and the thickness of the second internal electrode 122 after sintering may be 0.4 μm or less.

[0036] According to an embodiment, the dielectric layer 111 includes dielectric grains including a dielectric ceramic composition, and the dielectric ceramic composition includes a barium titanate (BaTiO3)-based matrix material main component and a subcomponent, wherein the subcomponent includes dysprosium (Dy) and praseodymium (Pr) as a first subcomponent. Based on 100 mol% of the matrix material main component, the content of Pr satisfies 0.233 mol%≤Pr≤0.699 mol%.

[0037] Recently, in order to develop ultra-small high-capacitance multilayer ceramic capacitors, it is necessary to develop a dielectric composition composition that can achieve a high dielectric constant by improving domain wall mobility when forming grains of the same size with a BaTiO3-based matrix material main component in which an additive is solid-dissolved.

[0038] Research results have shown that when donor-type dopant components are applied, the concentration of pinning sources in the lattice is reduced, thereby promoting the movement between domains.

[0039] To this end, among known donor-type dopants, additives having an ion size most similar to that of barium (Ba) may be applied to significantly reduce the lattice mismatch and develop a dielectric composition that allows realization of a high-k dielectric constant.

[0040] Generally, when the content of the donor type dopant is increased, the insulation resistance (IR) decreases and it is difficult to ensure the reduction resistance. Therefore, an appropriate content ratio tends to be selected.

[0041] The most commonly used donor-type dopant that has an impact on improving the dielectric constant and reliability of multilayer ceramic capacitors is dysprosium (Dy). The donor-type dopant and the acceptor-type dopant can be appropriately adjusted to achieve the desired dielectric properties and reliability.

[0042] The present inventors have invented a dielectric composition including praseodymium (Pr) as a rare earth element having a valence of +3 or more to chemically suppress the formation of oxygen vacancies and oxygen defects and reduce their concentration.

[0043] Since the ionic radius of the Pr element is approximately between the ionic radius of the barium (Ba) element (main element) and the ionic radius of the dysprosium (Dy) element (donor type dopant), the praseodymium (Pr) element effectively substitutes at the site of the Ba element and is solid-dissolved.

[0044] In an embodiment, the Pr element is applied together with the Dy element exhibiting stable dielectric characteristics, and an optimal content ratio is selected to ensure a high-k dielectric constant and improve reliability.

[0045] According to an embodiment, the dielectric ceramic composition includes a BaTiO3-based matrix material main component and a subsidiary component, the subsidiary component includes dysprosium (Dy) and praseodymium (Pr) as a first subsidiary component. Based on 100 mol % of the matrix material main component, the content of praseodymium (Pr) satisfies 0.233 mol % ≤ Pr ≤ 0.699 mol %.

[0046] The content of praseodymium (Pr) may be adjusted to satisfy 0.233 mol % ≤ Pr ≤ 0.699 mol % based on 100 mol % of the main component of the base material. Therefore, a high-k dielectric constant may be ensured, and reliability improvement such as increased insulation resistance may be achieved.

[0047] According to an embodiment, a dielectric ceramic composition of a dielectric layer included in a ceramic body includes rare earth elements dysprosium (Dy) and praseodymium (Pr) as subcomponents. The content of dysprosium (Dy) and praseodymium (Pr) may be controlled to ensure a high-k dielectric constant and achieve reliability improvement (such as increased insulation resistance).

[0048] When the content of praseodymium (Pr) is less than 0.233 mol % based on 100 mol % of the main component of the matrix material, the effect of increasing the dielectric constant is not large compared with the case where only dysprosium (Dy) is included.

[0049] When the content of praseodymium (Pr) exceeds 0.699 mol % based on 100 mol % of the main component of the base material, the insulation resistance decreases due to semiconductorization.

[0050] According to an embodiment, the total content of dysprosium (Dy) and praseodymium (Pr) may be 1.0 mol % or less based on 100 mol % of the main component of the matrix material.

[0051] Generally, as the total content of rare earth elements increases, it is more advantageous in terms of reliability, but the temperature characteristics deteriorate when Tc changes to room temperature. Therefore, specifically, the content of dysprosium (Dy) and praseodymium (Pr) can be adjusted to less than 1.0 mol% based on 100 mol% of the main component of the matrix material.

[0052] When the content of dysprosium (Dy) and praseodymium (Pr) is higher than 1.0 mol % based on 100 mol % of the main component of the base material, temperature characteristics such as temperature coefficient of capacitance (TCC) may be deteriorated.

[0053] According to an embodiment, the first subcomponent further includes an oxide or a carbonate including lanthanum (La), and the lanthanum (La) may be located at grain boundaries of dielectric grains.

[0054] When a rare earth element (eg, lanthanum (La)) having an ion radius greater than that of dysprosium (Dy) is used, lanthanum (La) can effectively replace the site of barium (Ba), thereby more effectively reducing the oxygen vacancy defect concentration.

[0055] Therefore, in order to improve reliability, lanthanum (La) may be further included as a first subcomponent to ensure insulation resistance while significantly reducing oxygen vacancy defect concentration.

[0056] However, when the content of lanthanum (La) is too high, the insulation resistance decreases rapidly due to excessive semiconductorization. Therefore, specifically, the content of lanthanum (La) may be greater than or equal to 0.233 mol% and less than or equal to 0.699 mol% based on 100 mol% of the main component of the base material.

[0057] As described above, the multilayer ceramic capacitor 100 according to the embodiment is an ultra-small high capacitance product, the dielectric layer 111 has a thickness of 0.4 μm or less, and the first and second internal electrodes 121 and 122 each have a thickness of 0.4 μm or less. However, their thicknesses are not limited thereto.

[0058] In addition, the size of the multilayer ceramic capacitor 100 may be 1005 (length×width, 1.0 mm×0.5 mm) or less.

[0059] For example, since the multilayer ceramic capacitor 100 according to the embodiment is an ultra-small high-capacitance product, the thickness of each of the dielectric layer 111 and the first and second internal electrodes 121 and 122 is smaller than that of the dielectric layer and the first and second internal electrodes of the product according to the related art. In the case of a product to which a thin dielectric layer and a thin internal electrode are applied, research on reliability improvement such as improvement of insulation resistance is a very important issue.

[0060] For example, since the thickness of the dielectric layer and the internal electrode included in the multilayer ceramic capacitor according to the prior art is greater than the thickness of the dielectric layer and the internal electrode of the multilayer ceramic capacitor according to the example, there is no significant problem with reliability even when the composition of the dielectric ceramic composition is the same as that according to the prior art.

[0061] However, in a product to which a thin dielectric layer and a thin internal electrode are applied as in the examples, the reliability of the multilayer ceramic capacitor is an important issue, and for this reason, the composition of the dielectric ceramic composition needs to be adjusted.

[0062] For example, in the embodiment, dysprosium (Dy) and praseodymium (Pr) are included as the first subcomponent in an amount of 1.0 mol% or less based on 100 mol% of the main component of the base material, and the content of praseodymium (Pr) is adjusted to satisfy 0.233 mol% ≤ Pr ≤ 0.699 mol% based on 100 mol% of the main component of the base material. Therefore, even in the case where the dielectric layer 111 is a thin film with a thickness of 0.4 μm or less, reliability improvement such as improved insulation resistance can be achieved.

[0063] However, “thin film” does not mean the fact that the thickness of each of the dielectric layer 111 and the first and second internal electrodes 121 and 122 is 0.4 μm or less, and can be understood as the thickness of the dielectric layer 111 and the first and second internal electrodes 121 and 122 being smaller than the thickness of the dielectric layer and the first and second internal electrodes of the product according to the related art.

[0064] Hereinafter, each component of the dielectric ceramic composition according to the embodiment will be described in further detail.

[0065] (A) Main components of matrix materials

[0066] The dielectric ceramic composition according to the embodiment may include a base material main component represented by BaTiO 3 .

[0067] According to an embodiment, the main component of the matrix material includes (Ba 1-x Cax )(Ti 1-y Ca y )O3 (where 0 ≤ x ≤ 0.3 and 0 ≤ y ≤ 0.1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (where 0 ≤ x ≤ 0.3 and 0 ≤ y ≤ 0.5), and Ba(Ti 1-y Zr y )O3 (0 < y ≤ 0.5), selected from the group consisting of, but not limited to.

[0068] The dielectric ceramic composition according to the embodiment may have a room temperature dielectric constant of 2000 or greater.

[0069] The main component of the base material is not limited, but the average particle size of the main component powder particles may be greater than or equal to 40 nm and less than or equal to 150 nm.

[0070] (B) First subcomponent

[0071] According to the embodiment, the dielectric ceramic composition substantially includes dysprosium (Dy) and praseodymium (Pr) as the first sub-components, and, based on 100 mol% of the main component of the base material, may further include an oxide or carbonate of lanthanum (La) in an amount greater than or equal to 0.233 mol% and less than or equal to 0.699 mol%.

[0072] The first sub-components can be used to prevent deterioration of the reliability of a multilayer ceramic capacitor to which the dielectric ceramic composition according to the embodiment is applied.

[0073] When the content of lanthanum (La) is less than 0.233 mol% based on 100 mol% of the main component of the base material, there is no effect of increasing the dielectric constant. When the content of lanthanum (La) is higher than 0.699 mol% based on 100 mol% of the main component of the base material, the insulation resistance will decrease, or the dissipation factor will decrease.

[0074] According to the embodiment, based on 100 mol% of the main component of the base material, the first sub-components may include dysprosium (Dy) and praseodymium (Pr) in an amount of 1.0 mol% or less, and based on 100 mol% of the main component of the base material, the content of praseodymium (Pr) can be adjusted to satisfy 0.233 mol% ≤ Pr ≤ 0.699 mol%. Therefore, even when the dielectric layer 111 is a thin film with a thickness of 0.4 μm or less, reliability improvements such as an increase in insulation resistance can be achieved.

[0075] When the content of praseodymium (Pr) is less than 0.233 mol % based on 100 mol % of the main component of the base material, the effect of increasing the dielectric constant is not large compared with the case of the related art including only dysprosium (Dy).

[0076] When the content of praseodymium (Pr) exceeds 0.699 mol % based on 100 mol % of the main component of the base material, the insulation resistance decreases due to semiconductorization.

[0077] (C) Second subcomponent

[0078] According to embodiments, the dielectric ceramic composition may include an oxide or a carbonate including at least one of Mn, V, Cr, Fe, Ni, Co, Cu, and Zn as a second subcomponent.

[0079] An oxide or carbonate including at least one of Mn, V, Cr, Fe, Ni, Co, Cu and Zn may be included as a second subcomponent in an amount of 0.1 mol % to 2.0 mol % based on 100 mol % of the main component of the base material.

[0080] The second subcomponent may be used to reduce the sintering temperature of a multilayer ceramic capacitor to which the dielectric ceramic composition is applied, and to improve high temperature withstand voltage characteristics.

[0081] The content of the second subcomponent and the contents of the third and fourth subcomponents described later may be defined as the contents included based on 100 moles of the base material main component, specifically, the moles of metal ions included in each subcomponent.

[0082] When the content of the second subcomponent is less than 0.1 mol % based on 100 mol % of the main component of the base material, the sintering temperature may increase and the high temperature withstand voltage characteristics may slightly deteriorate.

[0083] When the content of the second subcomponent is greater than 2.0 mol % based on 100 mol % of the main component of the matrix material, high temperature withstand voltage characteristics may be deteriorated and room temperature resistivity may be reduced.

[0084] Specifically, the dielectric ceramic composition according to the embodiment may include the second subcomponent in an amount of 0.1 mol % to 2.0 mol % based on 100 mol % of the main component of the matrix material. Therefore, low temperature sintering may be performed and high temperature withstand voltage characteristics may be obtained.

[0085] (D) The third subcomponent

[0086] According to an embodiment, the dielectric ceramic composition may include a third subcomponent which is an oxide or a carbonate including a fixed-valence acceptor element of magnesium (Mg).

[0087] The fixed valence acceptor element Mg may be included as a third subcomponent in an amount of 0.001 mol % to 0.5 mol % based on 100 mol % of the main component of the base material.

[0088] The third subcomponent is a fixed valence acceptor element or a compound including the same, and can be used as an acceptor to reduce electron concentration. By adding 0.001 mol% to 0.5 mol% of the fixed valence acceptor element Mg as the third subcomponent based on 100 mol% of the main component of the base material, the reliability improvement effect obtained by n-type conversion can be significantly improved.

[0089] When the content of the third subcomponent is more than 0.5 mol % based on 100 mol % of the main component of the matrix material, the dielectric constant may be reduced, which is disadvantageous.

[0090] According to an embodiment, 0.5 mol% of the third subcomponent may be added based on 100 mol% of the main component of the base material to significantly improve the reliability improvement effect obtained by n-type conversion. However, the content of the third subcomponent is not limited thereto, and the third subcomponent may be added in a small amount of 0.5 mol% or less based on 100 mol% of the main component of the base material.

[0091] (E) Fourth subcomponent

[0092] According to embodiments, the dielectric ceramic composition may include an oxide including at least one of silicon (Si) and aluminum (Al) or a glass compound including Si as a fourth subcomponent.

[0093] The dielectric ceramic composition may further include 0.001 mol % to 4.0 mol % of a fourth subcomponent which is an oxide including at least one of Si and Al or a glass compound including Si, based on 100 mol % of the main component of the base material.

[0094] The content of the fourth subcomponent may be based on the content of at least one of Si and Al included in the fourth subcomponent without distinguishing an addition form such as glass, oxide, or carbonate.

[0095] The fourth subcomponent may be used to reduce the sintering temperature of a multilayer ceramic capacitor to which the dielectric ceramic composition is applied, and improve high temperature withstand voltage characteristics.

[0096] When the content of the fourth subcomponent is more than 4.0 mol based on 100 mol of the main component of the matrix material, sinterability and density may be reduced and a secondary phase may be generated, which is disadvantageous.

[0097] Specifically, according to an embodiment, the dielectric ceramic composition may include aluminum (Al) in an amount of 4.0 mol or less based on 100 mol of the main component of the matrix material. Therefore, grain growth may be uniformly controlled to effectively improve withstand voltage characteristics and reliability, and improve DC bias characteristics.

[0098] Hereinafter, the present disclosure will be more fully described with reference to embodiments and comparative examples, which are intended to help detailed understanding of the present disclosure, but the scope of the present disclosure is not limited by the embodiments.

[0099] Example

[0100] In an embodiment, the dielectric layer can be formed by the following steps: adding additives (e.g., Dy, Pr, La, Al, Mg, Mn, etc.), binders, organic solvents (e.g., ethanol), etc. to dielectric material powder particles including barium titanate (BaTiO3) powder particles, performing wet mixing to prepare a dielectric slurry, and coating and drying the dielectric slurry on a carrier film to form a ceramic green sheet.

[0101] In this case, each of the additives of all elements having a size of 40% or less of barium titanate is monodispersed and added.

[0102] Specifically, the content of dysprosium (Dy) and praseodymium (Pr) among the rare earth elements is less than 1.0 mol % based on 100 mol % of the main component of the matrix material.

[0103] The embodiments include Example 1, Example 2, and Example 3. In Example 1, a ceramic green sheet is formed by adding 0.699 mol% of dysprosium (Dy) and 0.233 mol% of praseodymium (Pr). In Example 2, a ceramic green sheet is formed by adding 0.466 mol% of dysprosium (Dy) and 0.466 mol% of praseodymium (Pr). In Example 3, a ceramic green sheet is formed by adding 0.233 mol% of dysprosium (Dy) and 0.699 mol% of praseodymium (Pr).

[0104] The ceramic green sheet may be formed by mixing ceramic powder particles, a binder, and a solvent to prepare slurry; and manufacturing the slurry into a sheet having a thickness of several micrometers (μm) using a doctor blade method.

[0105] Then, a conductive paste for an internal electrode is prepared. The conductive paste may include 40 to 50 parts by weight of nickel powder particles having an average particle size of 0.1 to 0.2 μm based on 100 parts by weight of the conductive paste.

[0106] Conductive paste for internal electrodes is applied to the ceramic green sheets using a screen printing method to form internal electrodes. The green sheets on which the internal electrode patterns are formed are laminated to form a laminated body, which is then pressed and cut.

[0107] Then, the cut laminated body is heated to remove the binder, and sintered in a high-temperature reducing atmosphere to form a ceramic body.

[0108] During the sintering process, heat treatment was performed by sintering at 1100° C. to 1200° C. in a reducing atmosphere (0.1% H 2 / 99.9% N 2 , H 2 O / H 2 / N 2 atmosphere) for 2 hours, followed by further oxidation at 1000° C. in a nitrogen (N 2 ) atmosphere for 3 hours.

[0109] A termination process and electrode sintering are performed on the sintered ceramic body using a copper paste, and external electrodes are formed.

[0110] In addition, each of the dielectric layer 111 and the first and second internal electrodes 121 and 122 inside the ceramic body 110 is formed to have a thickness less than or equal to 0.4 μm after sintering.

[0111] (Comparative Example 1)

[0112] In the case of Comparative Example 1 which is an example according to the related art, 0.932 mol % of dysprosium (Dy) was added based on 100 mol % of the main component of the base material, and the other manufacturing processes were the same as those described in the above embodiment.

[0113] (Comparative Example 2)

[0114] In the case of Comparative Example 2, 0.932 mol % of praseodymium (Pr) was added based on 100 mol % of the main component of the base material, and the other manufacturing processes were the same as those described in the above embodiment.

[0115] The dielectric constant, dissipation factor (DF), and insulation resistance (IR) of Examples 1 to 3 and Comparative Examples 1 to 2 completed as prototype multilayer ceramic capacitor (MLCC) samples were tested, and the results thereof were evaluated.

[0116] The tests were performed under three conditions, respectively. The conditions of Test 1, Test 2, and Test 3 were 1140° C. (average 1135° C.), 1160° C. (average 1157° C.), and 1180° C. (average 1172° C.), respectively.

[0117] Table 1 lists the dielectric constant, dissipation factor (DF), and insulation resistance (IR) of prototype multilayer ceramic capacitor (MLCC) sheets according to experimental examples (Examples 1 to 3 and Comparative Examples 1 and 2).

[0118] Table 1

[0119]

[0120]

[0121] DF: Dissipation Factor / IR: Insulation Resistance / DC: Dielectric Constant

[0122] As can be seen from Table 1, in the case of Comparative Example 1 (0.932 mol % of dysprosium (Dy) was added based on 100 mol % of the main component of the base material), the dielectric constant DC was low and the insulation resistance IR was high.

[0123] In the case of Comparative Example 2 (the content of praseodymium (Pr) was higher than 0.699 mol % based on 100 mol % of the main component of the base material), a semiconductor tendency was shown, the dissipation factor DF was problematic, and the insulation resistance IR was deteriorated.

[0124] On the other hand, in Examples 1 to 3 of the present disclosure, the total content of dysprosium (Dy) and praseodymium (Pr) is 1.0 mol% or less based on 100 mol% of the main component of the base material, and the content of praseodymium (Pr) satisfies 0.233 mol%≤Pr≤0.699 mol%. A high-k dielectric constant can be ensured, and reliability improvement such as increased insulation resistance can be achieved.

[0125] Figure 3 is a graph showing temperature-dependent dielectric constant results according to embodiments and comparative examples in the present disclosure.

[0126] As from Figure 3 It can be seen that in the case of embodiment examples 1 to 3 (based on 100 mol% of the main component of the matrix material, the content of praseodymium (Pr) satisfies 0.233 mol%≤Pr≤0.699 mol%), the increase in the temperature-dependent dielectric constant is greater than the increase in the temperature-dependent dielectric constant of comparative example 1.

[0127] In the case of Comparative Example 2 (the content of praseodymium (Pr) was 0.932 mol % based on 100 mol % of the main component of the base material), the dielectric constant was high, but there was a tendency toward semiconductorization, resulting in a decrease in insulation resistance. Therefore, reliability was problematic.

[0128] As described above, the dielectric ceramic composition included in the dielectric layer inside the ceramic body may include a new rare earth element praseodymium (Pr) as a subcomponent, and the content of praseodymium (Pr) may be controlled to ensure a high-k dielectric constant, and reliability improvement such as increased insulation resistance may be achieved.

[0129] While example embodiments have been shown and described above, it will be apparent to those skilled in the art that modifications and variations may be made without departing from the scope of the present disclosure as defined by the appended claims.

Claims

1. A multilayer ceramic capacitor comprising: a ceramic body including a dielectric layer and first and second internal electrodes, the first and second internal electrodes being arranged to face each other with the respective dielectric layers interposed therebetween; and a first external electrode and a second external electrode disposed on an outer surface of the ceramic body, the first external electrode being electrically connected to the first internal electrode and the second external electrode being electrically connected to the second internal electrode, wherein the dielectric layer comprises dielectric grains containing a dielectric ceramic composition, and The dielectric ceramic composition comprises a main component of a matrix material and a subsidiary component, The main component of the matrix material includes at least one compound selected from the group consisting of the following compounds: (Ba 1- x Ca x )(Ti 1-y Ca y )O3, where 0 ≤ x ≤ 0.3 and 0 ≤ y ≤ 0.1; (Ba 1-x Ca x )(Ti 1-y Zr y )O3, where 0 < x ≤ 0.3 and 0 < y ≤ 0.5; and Ba(Ti 1-y Zr y )O3, where 0 < y ≤ 0.5, The subcomponents include Dy and Pr as first subcomponents, and Wherein, based on 100 mol% of the main component of the matrix material, the content of Pr satisfies 0.233 mol%≤Pr≤0.699 mol%, Wherein, based on 100 mol % of the main component of the matrix material, the total content of Dy and Pr is less than or equal to 1.0 mol %, and The first subcomponent further includes La, and La is included at grain boundaries of the dielectric grains.

2. The multilayer ceramic capacitor according to claim 1, wherein: The dielectric ceramic composition further includes 0.1 mol % to 2.0 mol % of a second subcomponent based on 100 mol % of a main component of the base material, the second subcomponent including at least one of Mn, V, Cr, Fe, Ni, Co, Cu and Zn.

3. The multilayer ceramic capacitor according to claim 2, wherein: The dielectric ceramic composition further includes 0.001 mol % to 0.5 mol % of a third subcomponent including a fixed-valence acceptor element Mg, based on 100 mol % of a main component of the base material.

4. The multilayer ceramic capacitor according to claim 3, wherein: The dielectric ceramic composition further includes 0.001 mol % to 4.0 mol % of a fourth subcomponent based on 100 mol % of a main component of the base material, and the fourth subcomponent includes at least one of Si and Al or a glass composite containing Si.

5. The multilayer ceramic capacitor according to claim 4, wherein: The thickness of the dielectric layer is 0.4 μm or less.

6. The multilayer ceramic capacitor according to claim 5, wherein: The inner electrode has a thickness of 0.4 μm or less.

7. The multilayer ceramic capacitor according to claim 6, wherein: The content of La is greater than or equal to 0.233 mol % and less than or equal to 0.699 mol % based on 100 mol % of the main component of the base material.

8. The multilayer ceramic capacitor according to any one of claims 1 to 7, wherein: The multilayer ceramic capacitor has a size of 1005 or less.

Citation Information

Patent Citations

  • Dielectric ceramic, method for manufacturing dielectric ceramic, and monolithic ceramic capacitor

    CN101006028A

  • Dielectric ceramic compositions and multilayer ceramic capacitors including the thereof

    CN112299840B